Changing libraries, encountering the law - Giannattasio, Isabelle (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
The technical and legal issues associated with digital material, originally the concern principally of audiovisual librarians, now impact upon library management in general. Three factors, occurring simultaneously, have driven the digital agenda for library managers: the high profile accorded to the accomplishment of mission; the ever-increasing complexity of copyright legislation; and the Internet which has served as a catalyst for deregulation and globalisation. The purpose of this short article is to explore both the opportunities and the obstacles posed by these factors across three core areas of digital collection management: conservation, access and development. I shall draw upon the Bibliothèque nationale de France (BnF) in this context. The BnF is a national library containing heritage collections, largely legal deposit and used for research purposes,. and also collections aimed at a far wider public.. The Audiovisual department is in charge of phonograms, videograms, multimedia and electronic documents. The collection was originally created in 1911 by the linguist Ferdinand Brunot of the Sorbonne University as ’Les Archives de la parole’. Subsequently the collection has been further developed mainly with published records, mostly as legal deposit. The collection now has over one million documents, in all kinds of technical devices and carriers. In France, three institutions share the audiovisual heritage collections: the BnF for documents, the Centre National de la Cinématographie (CNC) for film, and the Institut national de l’Audiovisuel for radio and television archives. In the BnF audiovisual collections are enlarged by legal deposit, by acquisitions and by donations. But whereas we own the carriers - a material property -, we do not own the intellectual property in the work. The protection of authors’ rights and neighbouring rights are central to the actions we have to perform in order to accomplish our missions of conservation and giving access.